High-frequency low-loss high-voltage ceramic dielectric material and preparation method thereof

CN118851746BActive Publication Date: 2026-08-11BEIJING QIXING FEIXING ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410861326.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2026-08-11
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

[0003]目前高压陶瓷电容器往往含有铅、镉,在制备和使用过程中对人体和环境均会造成危害,对性能也会产生一定的影响,不利于陶瓷电容器的安全性

Benefits of technology

[0024]本发明提供的高频低损耗高压陶瓷介质材料,以SrTiO3作为基体材料进行掺杂改性,通过掺杂少量CaSiTiO5和Mg3La2Ti6O18等原料制备的陶瓷电容器用瓷料,实现了耐直流电压>10kV/mm,介电常数最高>200,介电损耗<6×10-4、体积电阻率>1012Ω·cm,这些电性能的提高为制备高频低损耗高压陶瓷电容器奠定了良好的基础,能够满足送电、配电电力系统、高压电源、视频设备、处理脉冲能量设备等领域对陶瓷电容器的要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118851746B_ABST
    Figure CN118851746B_ABST
Patent Text Reader

Abstract

This invention relates to a high-frequency, low-loss, high-voltage ceramic dielectric material and its preparation method, the material comprising SrTiO3, CaTiO3, Bi2O3, TiO2, ZnO, CaSiTiO5, and Mg3La2Ti6O. 18 ZrO2 and MnCO3; to prepare this material, CaSiTiO5 and Mg3La2Ti6O2 need to be synthesized first. 18 Then the raw materials are mixed in proportion. This invention uses SrTiO3 as the matrix material for doping modification, by doping with small amounts of CaSiTiO5 and Mg3La2Ti6O. 18 The ceramic capacitor material prepared from raw materials achieves a DC voltage withstand capability >10kV / mm, a dielectric constant >200, and a dielectric loss <6×10⁻⁶. ‑4 Volume resistivity > 10 12 Ω·cm is used to prepare high-frequency, low-loss, high-voltage ceramic capacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high-frequency, low-loss, high-voltage ceramic dielectric material and its preparation method, belonging to the technical field of ceramic dielectric materials for capacitors. Background Technology

[0002] High-voltage ceramic capacitors are mainly used in power transmission and distribution systems, such as circuit breakers, voltage detectors, surge arresters, or devices that handle pulsed energy, such as gas lasers. In recent years, with advancements in materials, electrodes, and manufacturing technologies, high-voltage ceramic capacitors have developed rapidly and achieved widespread application. Because capacitors may operate in environments with high temperatures and humidity, the dielectric material must possess characteristics such as high withstand voltage, low loss, and high stability.

[0003] Currently, high-voltage ceramic capacitors often contain lead and cadmium, which can be harmful to human health and the environment during manufacturing and use, and also affect performance, compromising the safety of ceramic capacitors. Therefore, how to manufacture environmentally friendly ceramic dielectric materials for capacitors with high breakdown voltage, low loss, high volume resistivity, and high safety and reliability has become a key research focus for capacitors. Summary of the Invention

[0004] (a) Technical problems to be solved

[0005] To address the aforementioned problems in the prior art, this invention provides a high-frequency, low-loss, high-voltage ceramic dielectric material and its preparation method.

[0006] (II) Technical Solution

[0007] To achieve the above objectives, the main technical solutions adopted by the present invention include:

[0008] A high-frequency, low-loss, high-voltage ceramic dielectric material comprising SrTiO3, CaTiO3, Bi2O3, TiO2, ZnO, CaSiTiO5, and Mg3La2Ti6O 18 ZrO2 and MnCO3.

[0009] Further, it comprises, by weight, 60-80 parts of SrTiO3, 9-35 parts of CaTiO3, 0.1-5 parts of Bi2O3, 0.1-5 parts of TiO2, 0.1-5 parts of ZnO, 0.1-5 parts of CaSiTiO5, and 0.1-5 parts of Mg3La2Ti6O. 18 0.1–5 parts, ZrO2 0.1–6 parts and MnCO3 0.1–5 parts.

[0010] In a preferred embodiment, the raw materials of the high-frequency, low-loss, high-voltage ceramic dielectric material as described above, by weight, are: SrTiO3 60-80 parts, CaTiO3 12-35 parts, Bi2O3 0.3-3 parts, TiO2 0.1-2 parts, ZnO 0.5-3 parts, CaSiTiO5 1-3 parts, Mg3La2Ti6O 18 0.1-2 parts, ZrO2 0.2-4 parts, MnCO3 0.1-2 parts.

[0011] In another preferred embodiment, the raw materials of the high-frequency, low-loss, high-voltage ceramic dielectric material as described above, by weight, are: SrTiO3 60-70 parts, CaTiO3 25-35 parts, Bi2O3 0.3-2 parts, TiO2 0.2-2 parts, ZnO 0.1-2 parts, CaSiTiO5 1.5-2.5 parts, Mg3La2Ti6O 18 0.1–1.5 parts, ZrO2 0.3–3.8 parts, MnCO3 0.5–1.5 parts.

[0012] In another preferred embodiment, the raw materials of the high-frequency, low-loss, high-voltage ceramic dielectric material as described above, by weight, are: SrTiO3 65 parts, CaTiO3 31.3 parts, Bi2O3 0.3 parts, TiO2 0.5 parts, ZnO 0.3 parts, CaSiTiO5 1.2 parts, Mg3La2Ti6O 18 0.7 parts, ZrO2 0.6 parts, MnCO3 0.1 parts.

[0013] The high-frequency, low-loss, high-voltage ceramic dielectric material described above, preferably, comprises SrTiO3, CaTiO3, CaSiTiO5, and Mg3La2Ti6O. 18 They were synthesized using solid-state methods.

[0014] The method for preparing SrTiO3 is as follows: raw materials SrCO3 and TiO2 are mixed in a 1:1 molar ratio, ball-milled and dried at 110-140℃, and then kept at 1250℃-1290℃ for 2.5-3.5 hours to synthesize SrTiO3 through solid-phase reaction.

[0015] The method for preparing CaTiO3 is as follows: CaCO3 and TiO2 are mixed in a 1:1 molar ratio, ball-milled and dried at 110-140℃, and then kept at 1230℃-1270℃ for 2.5-3.5 hours to synthesize CaTiO3 by solid-phase reaction.

[0016] The method for preparing CaSiTiO5 is as follows: raw materials CaCO3, SiO2 and TiO2 are mixed in a molar ratio of 1:1:1, ball-milled and dried at 110-140℃, and then kept at 1200-1300℃ for 3-4 hours to synthesize CaSiTiO5 through solid-phase reaction.

[0017] The Mg3La2Ti6O 18 The preparation method is as follows: raw materials La2O3, MgCO3, and TiO2 are mixed in a molar ratio of 1:3:6, ball-milled, and dried at 110–140℃. Then, the mixture is kept at 1200℃–1300℃ for 3–4 hours to synthesize Mg3La2Ti6O through a solid-state reaction. 18 .

[0018] The high-frequency, low-loss, high-voltage ceramic dielectric material described above, preferably, comprises SrTiO3, CaTiO3, and Mg3La2Ti6O. 18 Both CaSiTiO5 and CaSiTiO5 need to be passed through a 180-mesh sieve after grinding.

[0019] The preparation method of the high-frequency, low-loss, high-pressure ceramic dielectric material as described above preferably involves preparing each raw material according to the weight proportions, then ball milling and mixing, adding a binder for granulation, drying in an oven, and sieving the dried granules to obtain the high-frequency, low-loss, high-pressure ceramic dielectric material.

[0020] In the preparation method described above, preferably, the ball milling is performed for 3-4 hours, the binder is an 8% (w / w) polyvinyl alcohol aqueous solution, and the ball milling is performed for 0.5-1.5 hours after adding the binder; the drying temperature is 130-150℃, and the dried granules are passed through a 70-mesh sieve.

[0021] A high-frequency, low-loss, high-voltage ceramic capacitor is obtained by pressing the high-frequency, low-loss, high-voltage ceramic dielectric material as described above, holding it at a high temperature of 1300-1350°C for 1.5-2 hours to obtain the ceramic capacitor body, and then sintering, welding, and encapsulating the ceramic body with silver to obtain the high-frequency, low-loss, high-voltage ceramic capacitor.

[0022] (III) Beneficial Effects

[0023] The beneficial effects of this invention are:

[0024] The high-frequency, low-loss, high-voltage ceramic dielectric material provided by this invention uses SrTiO3 as the matrix material and performs doping modification by doping with small amounts of CaSiTiO5 and Mg3La2Ti6O. 18 The ceramic capacitor material prepared from raw materials achieves a DC voltage withstand capability >10kV / mm, a dielectric constant >200, and a dielectric loss <6×10⁻⁶. -4 Volume resistivity > 10 12The improved electrical properties, such as Ω·cm, lay a solid foundation for the fabrication of high-frequency, low-loss, high-voltage ceramic capacitors, which can meet the requirements of ceramic capacitors in fields such as power transmission and distribution systems, high-voltage power supplies, video equipment, and pulse energy processing equipment. Attached Figure Description

[0025] Figure 1 This is a schematic diagram of the preparation method of the present invention. Detailed Implementation

[0026] The ceramic dielectric material of this invention uses SrTiO3 as the main material, and is doped with small amounts of CaSiTiO5 and Mg3La2Ti6O. 18 The fusing material improves the DC voltage withstand capability of the ceramic material (>10kV / mm) and reduces the dielectric loss (<6×10). -4 Volume resistivity > 10 12 Ω·cm.

[0027] SrTiO3 exhibits a typical perovskite structure, is in the paraelectric phase at room temperature, and has a Curie temperature of approximately -250℃. Because pure SrTiO3 has a high leakage current, the structure of SrTiO3 ceramics can be adjusted by doping, for example, by A-site substitution of Pb. 2+ Ba 2+ Si replaced at B site 4+ Zr 4+ When rare earth elements are doped, relaxation occurs, and the corresponding permittivity and dielectric properties also increase. Existing technologies have ceramic materials with dielectric constants greater than 3500 and DC withstand voltages greater than 14kV / mm, but losses are greater than 100×10⁻⁶. -4 Therefore, SrTiO3 is used as the matrix material for doping modification, but some raw materials need to be pre-synthesized into frits before doping. Meanwhile, in order to comply with the trend of lead-free and environmentally friendly materials, the ceramic material involved in this invention does not contain harmful elements such as lead and cadmium.

[0028] The preferred dosage of CaSiTiO5 is between 0.1 and 5 parts, which can reduce the loss of ceramic dielectric materials and increase the DC voltage resistance.

[0029] Among them, Mg3La2Ti6O 18 The preferred dosage is between 0.1 and 5 parts, which can improve the dielectric constant and regulate the temperature characteristics.

[0030] To better explain and facilitate understanding of this invention, the following description is provided in conjunction with the appendix. Figure 1 The present invention will be described in detail through specific embodiments.

[0031] Example 1

[0032] The main raw materials used in the 15 sample formulations of this invention are of industrial grade purity. During preparation, conventional chemical raw materials are first used to synthesize frits via a solid-state method: SrTiO3, CaTiO3, CaSiTiO5, Mg3La2Ti6O 18 .

[0033] The preparation method of SrTiO3 involved in this invention is as follows: raw materials SrCO3 and TiO2 are mixed in a 1:1 molar ratio, ball-milled and dried at 140°C, and then placed in an alumina crucible and kept at 1260°C for 3 hours to synthesize SrTiO3 through solid-phase reaction. After cooling, it is ground through an 180-mesh sieve.

[0034] The method for preparing CaTiO3 involved in this invention is as follows: CaCO3 and TiO2 are mixed in a 1:1 molar ratio, ball-milled and dried at 140°C, and then placed in an alumina crucible and kept at 1250°C for 3 hours to synthesize CaTiO3 through solid-phase reaction. After cooling, it is ground through an 180-mesh sieve for later use.

[0035] The method for preparing CaSiTiO5 involved in this invention is as follows: CaCO3, SiO2 and TiO2 are mixed in a molar ratio of 1:1:1, ball-milled and dried at 140°C, and then placed in an alumina crucible and kept at 1250°C for 3 hours to synthesize CaSiTiO5 through solid-phase reaction. After cooling, it is ground through an 180-mesh sieve for later use.

[0036] The Mg3La2Ti6O involved in this invention 18 The preparation method is as follows: raw materials La2O3, MgCO3, and TiO2 are mixed in a molar ratio of 1:3:6, ball-milled, and dried at 140℃. Then, the mixture is placed in an alumina crucible and kept at 1270℃ for 3 hours to synthesize Mg3La2Ti6O through a solid-state reaction. 18 After cooling, grind through a 180-mesh sieve for later use.

[0037] Take, by weight, 60 parts of SrTiO3, 34.5 parts of CaTiO3, 1.2 parts of CaSiTiO5, and Mg3La2Ti6O3 prepared according to the above preparation method. 180.5 parts of Bi₂O₃, 1.2 parts of TiO₂, 0.4 parts of ZnO, 0.8 parts of ZrO₂, and 0.6 parts of MnCO₃ by weight were added and then mixed. The mixed materials were then ball-milled in distilled or deionized water for 3 hours, with a material:ball:water mass ratio of 1:3:0.8. Then, an 8% polyvinyl alcohol solution was added, and after ball-milling for 1 hour, granulation was performed. The granules were dried in an oven at 140°C, and then passed through a 70-mesh sieve to obtain the high-frequency, low-loss, high-pressure ceramic dielectric material. This material was then pressed to a density of 3.2 g / cm³ using a 25-ton mechanical press. 3 The green body was heated at 1320℃ for 2 hours to obtain the ceramic body of the high-frequency, low-loss, high-voltage ceramic capacitor. Silver electrodes were then applied to both sides of the obtained ceramic body, and the silver was fired at 850℃. Afterwards, leads were soldered, and the ceramic capacitor was encapsulated with epoxy resin to obtain the ceramic capacitor. The electrical performance of the obtained ceramic capacitor was tested, and the results are shown in Table 2.

[0038] The electrical performance measurement of the ceramic dielectric material for capacitors involved in this invention is performed in accordance with the relevant requirements of GB / T5596-1996, specifically:

[0039] The method for testing the electrical properties of the ceramic dielectric material is as follows:

[0040] The capacitance and loss of the ceramic dielectric material were tested using an E4981A capacitance meter. The test voltage was 1±0.2V, the test frequency was 1MHz, and the test temperature was 25±2℃. The dielectric constant was calculated using the following formula:

[0041] ε=14.4·C·h / D 2

[0042] Where ε is the permittivity (dielectric constant);

[0043] C is the capacitance of the sample, pF;

[0044] h is the thickness of the medium, in cm;

[0045] D is the electrode diameter, in cm.

[0046] The insulation resistance value of the ceramic dielectric material was tested using a TH2681A insulation resistance tester at a test voltage of 100V and a test temperature of 25±2℃.

[0047] The DC insulation strength of the ceramic dielectric material was tested using a CS2674AX withstand voltage tester at a temperature of 25±2℃.

[0048] The temperature coefficient of capacitance of the ceramic dielectric material was tested using an MC-711 high and low temperature test chamber at 20℃ and 85℃.

[0049] Example 2-15

[0050] The ceramic dielectric materials of Examples 2-15 were prepared according to the formulation composition in Table 1 using the same preparation method as in Example 1, and the electrical properties of the prepared ceramic capacitors were tested using the same test methods and conditions as in Example 1. The test results of the electrical properties of the ceramic capacitors prepared according to the formulations of Examples 2-15 are shown in Table 2.

[0051] Table 1. Formulation composition of Examples 1-15 of the present invention

[0052]

[0053] Table 2 Electrical properties of the formulation samples in Examples 1-15

[0054]

[0055]

[0056] Comparative Example 1

[0057] This invention includes nine comparative samples. The raw materials used in the formulations are prepared using the same method as those in Example 1 for preparing high-frequency, low-loss, high-voltage ceramic dielectrics, namely, SrTiO3, CaTiO3, CaSiTiO5, and Mg3La2Ti6O4 using industrial-grade raw materials in solid-state synthesis. 18 Fused material. Taking sample formulation number 1 as an example, the fused material contains 60 parts by weight of SrTiO3, 32.2 parts of CaTiO3, 0 parts of CaSiTiO5, and Mg3La2Ti6O3. 18 4.2 parts by weight of Bi₂O₃, 1.5 parts by weight of TiO₂, 0.4 parts by weight of ZnO, 0.1 parts by weight of ZrO₂, and 0.8 parts by weight of MnCO₃ were prepared. The prepared materials were then mixed with distilled or deionized water in a ball mill at a mass ratio of 1:3:0.8 for 3 hours. An 8% polyvinyl alcohol solution was then added, and the mixture was ball-milled for another hour before granulation. The granules were then dried in an oven at 140°C. The dried granules were passed through a 70-mesh sieve to obtain the high-frequency, low-loss, high-pressure ceramic dielectric material. This material was then pressed to a density of 3.2 g / cm³ using a 25-ton mechanical press. 3The green body was heated at 1310℃ for 2 hours to obtain the ceramic body of the high-frequency, low-loss, high-voltage ceramic capacitor. Silver electrodes were then applied to both sides of the obtained ceramic body, and the silver was fired at 850℃. Afterwards, leads were soldered, and the ceramic capacitor was encapsulated with epoxy resin to obtain the ceramic capacitor. The electrical performance of the obtained ceramic capacitor was tested using the same test methods and conditions as in Examples 1-15. The electrical performance test results of the ceramic capacitor prepared with the ceramic dielectric material of Comparative Example 1 are shown in Table 4.

[0058] Comparative Examples 2-9

[0059] Following the formulations in Table 3, ceramic dielectric materials for Comparative Examples 2-9 were prepared using the same preparation method as in Comparative Example 1. The electrical properties of the prepared ceramic capacitors were tested using the same testing methods and conditions as in Examples 1-15. The test results of the electrical properties of the ceramic capacitors prepared using the formulations in Comparative Examples 2-9 are shown in Table 4.

[0060] Table 3. Formulation composition of comparative samples 1-9

[0061]

[0062] Table 4 Electrical properties of comparative sample 1-9

[0063]

[0064] As can be seen from Tables 2 and 4, different frits and frit doping ratios can affect the electrical properties of ceramic dielectric materials. In Examples 1-15, CaSiTiO5 and Mg3La2Ti6O were added... 18 The DC insulation strength was obtained as >10kV / mm, the dielectric constant as >200, and the loss tangent as <5×10⁻⁶. -4 Volume resistivity ≥10 12 Ceramic dielectric material with Ω·cm.

[0065] Comparative sample 1-9 of this invention are doped only with CaSiTiO5 or Mg3La2Ti6O 18 The ceramic dielectric material of the fused block has the following electrical properties: DC insulation strength > 8 kV / mm, dielectric constant > 200, and loss tangent < 7 × 10⁻⁶. -4 Volume resistivity ≥10 11 Ω·cm.

[0066] As can be seen from the comparison of the electrical properties of ceramic dielectric materials in Tables 2 and 4, comparative sample 1-9 were only doped with a single CaSiTiO5 or Mg3La2Ti6O 18When the ceramic capacitor is fused together, its electrical properties cannot simultaneously meet the requirements of high DC insulation strength, high volume resistivity, and low loss. Examples 1-15 simultaneously dope CaSiTiO5 and Mg3La2Ti6O 18 The fused metal can achieve a DC insulation strength >10kV / mm, a dielectric constant >200, and a loss tangent <6×10⁻⁶. -4 Volume resistivity ≥10 12 Ω·cm.

[0067] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any other way. Any person skilled in the art can make changes or modifications to the above-disclosed technical content to create equivalent embodiments. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention.

Claims

1. A high-frequency, low-loss, high-voltage ceramic dielectric material, characterized in that, It consists of, by weight, 60-80 parts of SrTiO3, 9-35 parts of CaTiO3, 0.1-5 parts of Bi2O3, 0.1-5 parts of TiO2, 0.1-5 parts of ZnO, 0.1-5 parts of CaSiTiO5, and 0.1-5 parts of Mg3La2Ti6O. 18 Prepared from 0.1–5 parts of ZrO2, 0.1–6 parts of ZrO2, and 0.1–5 parts of MnCO3; Among them, Mg3La2Ti6O 18 The preparation method is as follows: raw materials La2O3, MgCO3 and TiO2 are mixed in a molar ratio of 1:3:6, ball-milled and dried at 110-140℃, and then kept at 1200-1300℃ for 2-3 hours to synthesize Mg3La2Ti6O through solid-state reaction. 18 .

2. The high-frequency, low-loss, high-voltage ceramic dielectric material as described in claim 1, characterized in that, SrTiO3 60-80 parts, CaTiO3 12-35 parts, Bi2O3 0.3-3 parts, TiO2 0.1-2 parts, ZnO 0.5-3 parts, CaSiTiO5 1-3 parts, Mg3La2Ti6O 18 0.1-2 parts, ZrO2 0.2-4 parts, MnCO3 0.1-2 parts.

3. The high-frequency, low-loss, high-voltage ceramic dielectric material as described in claim 1, characterized in that, The preparation method of SrTiO3 is as follows: raw materials SrCO3 and TiO2 are mixed in a 1:1 molar ratio, ball-milled and dried at 110-140℃, and then kept at 1250℃-1290℃ for 2.5-3.5 hours to synthesize SrTiO3 by solid-phase reaction. The method for preparing CaTiO3 is as follows: CaCO3 and TiO2 are mixed in a 1:1 molar ratio, ball-milled and dried at 110-140℃, and then kept at 1230℃-1270℃ for 2.5-3.5 hours to synthesize CaTiO3 by solid-phase reaction.

4. The high-frequency, low-loss, high-voltage ceramic dielectric material as described in claim 1, characterized in that, The preparation method of CaSiTiO5 is as follows: raw materials CaCO3, SiO2 and TiO2 are mixed in a molar ratio of 1:1:1, ball-milled and dried at 110-140℃, and then kept at 1200℃-1300℃ for 2-3 hours to synthesize CaSiTiO5 through solid-phase reaction.

5. The high-frequency, low-loss, high-voltage ceramic dielectric material as described in claim 1, characterized in that, The SrTiO3, CaTiO3, Mg3La2Ti6O 18 CaSiTiO5 needs to be ground through a 180-mesh sieve.

6. The method for preparing the high-frequency, low-loss, high-voltage ceramic dielectric material according to any one of claims 1-5, characterized in that, It includes preparing each raw material according to the weight proportions, then ball milling and mixing, adding a binder, granulating and drying to obtain a high-frequency, low-loss, high-pressure ceramic dielectric material.

7. The preparation method according to claim 6, characterized in that, The ball milling process lasts for 3-4 hours. The binder is an 8% (w / w) polyvinyl alcohol aqueous solution. After adding the binder, the ball milling process lasts for 0.5-1.5 hours. The drying temperature is 130-150°C. The dried granules are then passed through a 70-mesh sieve.

8. A high-frequency, low-loss, high-voltage ceramic capacitor, characterized in that, The process involves pressing the high-frequency, low-loss, high-voltage ceramic dielectric material as described in claim 1 or 2, holding it at a high temperature of 1300–1350°C for 1.5–2 hours to obtain a ceramic capacitor body, which is then silvered, sintered, welded, and encapsulated to obtain a high-frequency, low-loss, high-voltage ceramic capacitor.

Citation Information

Patent Citations

  • Microwave medium material and preparation method thereof

    CN104446442A

  • Dielectric material for preparing small-loss ultrahigh-voltage alternating-current ceramic dielectric capacitor and preparation method thereof

    CN115959904A